Enhancing Lecturer Productivity Through Work-Life Balance and Organizational Commitment: The Moderating Role of Information Technology in Islamic Universities - Ahmad Yani; Suharno Pawirosumarto; Muhammad Ridwan (Dinasti International Journal of Education Management and Social Science, 2026)
Lecturer productivity is a strategic priority for Islamic Higher Education Institutions (IHEIs), which combine academic excellence with Islamic values and community service while often operating under constraints such as limited digital infrastructure, heavy administrative workloads, and dual religious–academic responsibilities. This study examines how organizational commitment and work-life balance influence lecturer productivity in six IHEIs in Jambi Province, with information technology (IT) tested as a moderating factor. Using a quantitative survey of 237 lecturers and analyzing the data with SEM-PLS, the results show that organizational commitment significantly improves lecturer productivity, whereas work-life balance has a positive but statistically insignificant effect. IT demonstrates a strong direct impact on productivity, but it does not moderate the effects of organizational commitment or work-life balance, suggesting that technology operates primarily as a general performance enabler rather than a conditional amplifier of these individual factors. These findings extend evidence on productivity determinants in the under-studied IHEI context and offer practical implications for policy and management, particularly the need to strengthen digital infrastructure, enhance organizational support systems, and align HR practices with the institutional realities of Islamic higher education.